Insurance Innovations as a Part of the Financial Inclusion - Iryna Didenko; Natalia Sidelnyk (Business Ethics and Leadership)
This paper summarizes the arguments and counterarguments within the scientific discussion on the main trends in insurance innovations. The research’s primary purpose is to identify the place and role of insurance innovations in today’s financial services market. Systematization of literary sources and approaches to solve the problem of introducing innovative processes in the insurance business development demonstrated that today in the conditions of global digitalization, the direction of insurance tech development is gaining popularity. The paper draws a parallel between the level of financial literacy of the population, as its ability to perceive new financial products and services, and financial inclusion, as a willingness to be an active user in the financial services market with the popularity of insurance policies for both life and non-life insurance. Research conducted by the World Bank in 2014 and the International Monetary Fund in 2019 did not reveal a direct relationship between the level of financial literacy of the population and the level of activity in the use of insurance services. At the same time, there is a high rate of growth in the dynamics of insurance services (non-life insurance in particular) in countries where there is an active process of development of innovative digital technologies (China, India, Taiwan, Japan). The research methods’ methodological tools were analytical tools of the Scopus database and VOSviewer software years of research during 2012 – 2021. According to the international Scopus database results, the object of study is the chosen countries, regions, and industries. The paper presents empirical bibliographic analysis results, which showed that today most research is conducted by experts from the USA (more than 800 publications), Great Britain (more than 150 publications), India, and China (more than 120 publications), and Germany. These countries, especially China and India, demonstrate the rapid development and introduction of innovative digital technologies in the insurance sector. The research empirically confirms and theoretically proves that insurance innovations are an integral and integral part of the financial sector as a whole. In addition, the main vectors of development of innovative co-concept in the field of insurance are highlighted: machine learning, forecasting analytics, consumer protection system in the information space, the concept of “unstructured data”, artificial intelligence, blockchain technology, telematics. The results of the research can be helpful for further scientific work.